Dynamics of magma mixing and magma mobilisation beneath Mauna Loa: insights from the 1950 AD Southwest Rift Zone eruption - Kahl, Maren; Morgan, Daniel J.; Thornber, Carl; Walshaw, Richard; Lynn, Kendra J.; Trusdell, Frank A. (Bulletin of volcanology, 2023)
Eruptions from Mauna Loa’s Southwest Rift Zone (SWRZ) pose a significant threat to nearby communities due to high eruption rates and steep slopes resulting in little time for evacuation. Despite the large body of research done on Mauna Loa, knowledge of the timing and duration of magma residence and transfer through its internal plumbing system is still poorly constrained. This study presents a first quantitative look at thermochemical conditions and timescales of potentially deep storage and disaggregation of magmatic mush during the run-up to the voluminous 1950 AD SWRZ eruption. Details of heterogeneous compositions and textures of the macrocryst and glomerocryst cargo in 1950 AD lavas suggest magma mixing and crystal recycling along the entire plumbing system. Furthermore, the crystal cargo contains evidence for the direct interaction between primitive, deeply stored magma and pockets of more evolved magma stored at shallow to intermediate depths. An enigmatic attribute of 1950 near-vent lava is the near-ubiquitous presence of subhedral, unreacted Mg-rich orthopyroxene phenocrysts (Mg#>80). Phase relations of Mauna Loa olivine-tholeiite indicate that orthopyroxene joins olivine as a primary phase at pressures higher than 0.6 GPa. Coexisting Mg-rich olivine and orthopyroxene and the occurrence of harzburgitic (olivine-orthopyroxene) glomerocrysts provide evidence for cognate crystallisation at near-Moho (~ 18 km) depths (Thornber and Trusdell 2008). Petrogenetically diverse populations of glomerocrysts and macrocrysts alongside evidence of multilevel magma storage indicate a network of ephemeral and possibly interconnected magma pockets from near-Moho depths to the upper/mid-crust. Fe-Mg diffusion chronometry applied to 1950 AD olivine populations implies rapid mobilisation and transport of large volumes of magma (376×106 m3) from near-Moho storage to the surface within less than 8 months, with little residence time (~ 2 weeks) in the shallow (3-5 km) plumbing system.
Gesehen am 26.01.2024